(untitled) (Medical Forum Monthly, 2024)
Objective: The aim of this study is to evaluate the clinical presentation and drug resistance patterns of Salmonellae typhi & paratyphi Study design: Observational Descriptive Study. Place and Duration: This study was conducted at the Muhammad Medical Hospital Mirpurkhas, from Jan 2010 to April 2011. Materials and Methods: One hundred twenty six patients were studied, who satisfied the clinical and laboratory criteria of typhoid/paratyphoid fever. The blood samples, 5–10 ml from adults were inoculated directly into blood culture bottles. Subcultures were also performed. Antibiotic sensitivity was tested by the Kirby–Bauer technique according to Clinical and Laboratory Standards Institute guidelines. Statistical analysis was performed on SPSS version 10.0. (Chicago, Illinosis, USA), using the chi-square test and student’s t-test for the qualitative and quantitative variables respectively. Results: The identified organisms were S.typhi observed in 91 (72.22%), both S typhi/paratyphi in 18 (14.28%) and S.paratyphi A and B in the rest 17 (13.49%). In 97 (76.98%) of patients, antibody O titers were ≥1:160 and in 39 (30.95%) titers were <1:160. The overall multi-drug resistant isolates were found in >80% for the first line agent’s i.e.; ampicillin, amoxicillin, cotrimoxazole and chloramphenicol. The highest sensitivity rate was found for the cefixime (98.41%) and the lowest one for the ampicillin (22.2%). Conclusions: We found drug resistant and multi-drug resistant salmonellae in our study; this may be because of antibiotic use as self medication, medication by pharmacist and quacks